Existence of Two Solutions for a Critical Elliptic Problem with Nonlocal Term in ℝ4. (20th June 2022) - Sabri, Khadidja; Matallah, Atika; Benmansour, Safia; El Mokhtar, Mohammed El Mokhtar Ould
Abstract : In this paper, we prove the existence of two positive solutions for a critical elliptic problem with nonlocal term and Sobolev exponent in dimension four.